การศึกษาผลสัมฤทธิ์ทางการเรียนเรื่องสัญลักษณ์ทางดนตรีสากลด้วยการเรียนเชิงรุกโปรแกรม Music Learning ของนักเรียนชั้นประถมศึกษาปีที่ 3 โรงเรียนเซนต์โยเซฟคอนเวนต์ กรุงเทพมหานคร - บุญหลง, รัตติยา; หวังพานิช, ฌานิก (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การเรียนเชิงรุกเป็นการเรียนที่เน้นให้ผู้เรียนได้มีส่วนร่วมในการจัดประสบการณ์เพื่อพัฒนาผู้เรียนให้เป็นผู้มีทักษะการคิดวิเคราะห์ การทำงานร่วมกันและการแก้ปัญหา ซึ่งเป็นทักษะที่จำเป็นในศตวรรษที่ 21 ในการวิจัยนี้เป็นการวิจัยกึ่งทดลอง ผู้วิจัยได้พัฒนารูปแบบการเรียนเชิงรุกและโปรแกรม Music Learning ซึ่งเป็นโปรแกรมคอมพิวเตอร์ดนตรีช่วยสอน โดยมีวัตถุประสงค์เพื่อศึกษาผลสัมฤทธิ์ทางการเรียน เรื่องสัญลักษณ์ทางดนตรีสากล ด้วยการเรียนเชิงรุก โปรแกรม Music Learning และศึกษาความคิดเห็นที่มีต่อการเรียนเชิงรุก โปรแกรม Music Learning กลุ่มตัวอย่างเป็นนักเรียนชั้นประถมศึกษาปีที่ 3 โรงเรียนเซนต์โยเซฟคอนเวนต์ กรุงเทพมหานคร จำนวน 28 คน ที่เรียนกิจกรรมดนตรี ในภาคเรียนที่ 2 ปีการศึกษา 2562 เครื่องมือที่ใช้ในการวิจัย คือ เครื่องมือที่ใช้ในการทดลอง ได้แก่ แผนการจัดการเรียนรู้ด้วยการเรียนเชิงรุก และโปรแกรม Music Learning เรื่องสัญลักษณ์ทางดนตรีสากล และเครื่องมือรวบรวมข้อมูล ได้แก่ แบบทดสอบผลสัมฤทธิ์ทางการเรียน เรื่องสัญลักษณ์ทางดนตรีสากล และแบบสอบถามความคิดเห็นที่มีต่อการเรียนเชิงรุก โปรแกรม Music Learning วิเคราะห์ข้อมูลโดยใช้สถิติพื้นฐาน และเปรียบเทียบผลสัมฤทธิ์ทางการเรียนก่อนและหลังการทดลอง โดยใช้ t-test แบบ Dependent sample ผลการวิจัยพบว่า 1) นักเรียนที่เรียนสัญลักษณ์ทางดนตรีสากลด้วยการเรียนเชิงรุกโปรแกรม Music Learning มีผลสัมฤทธิ์ทางการเรียนสัญลักษณ์ทางดนตรีสากลทั้งรายบุคคลและโดยรวมสูงขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 2) นักเรียนมีความคิดเห็นต่อการเรียนเชิงรุกโปรแกรม Music Learning ว่ามีความเหมาะสมในระดับมากที่สุดผลของการวิจัยนี้จะเป็นข้อมูลในการพัฒนาหรือปรับปรุงการเรียนการสอนดนตรีในศตวรรษที่ 21 ให้มีประสิทธิผลมากขึ้น คำสำคัญ: สัญลักษณ์ทางดนตรีสากล, การเรียนเชิงรุก, โปรแกรม Music Learning Abstract Active learning is learning that focuses on the learners to be involved in the experiences to develop the learning to have critical thinking, collaboration and problem-solving skills which are necessary skills in the 21st century. This research is quasi-experimental research in which the researcher developed the active learning model and Music Learning program which is a computer assisted music instruction. It aims to examine learning achievement on music symbols using active learning with the Music Learning Program; and to study the opinions of the students towards active learning with the Music Learning Program. The sample consisted twenty-eight Prathom Suksa Three students enrolled in Musical Activity Club in the second semester of the 2019 academic year. The research tools included the experimental tool which is the active learning lesson plan and the Music Learning Program on music symbols; and the data-collection tools including the achievement on the music symbols test and the questionnaire on the active learning with the Music Learning Program. The results derived from the data were calculated using a simple descriptive statistical analysis and also comparison of learning achievement before and after the experiment using t-test for Dependent sample. The findings were as follows: 1) the students taking the active learning the Music Learning Program significantly increased their learning achievement in music symbols both individually and overall, with a statistical significance of .05; and 2) the students expressed their opinion on active learning with the Music Learning Program with mostly appropriate. According to results of this research, it will be the information to develop or improve be more effective music teaching and learning in the 21st century. Keywords: Music symbols, Active Learning, Music Learning Program